Smart home - Mohamad Hussin, Mohamad Amirul; Zulkiflee, Izzat Yazid (2016)
Lifestyle in the modem society along with human behaviour and thinking is changing dramatically with the advancement of technology, and the concept of a simple home is changing into a smart home. The advancement of technology has increased the safety and security of people along with their belongings and lead to the necessity of keeping surveillance over their homes. There are different types of built smart home systems, and they do not have flexibility over choosing the types and number of sensors used and the cost of the system. These systems are prebuilt devices with a limited number of sensors, with a limited area of coverage. The application consisted of two units, Arduino Uno and the mobile unit. The mobile unit acted as a recipient to get responses from the Arduino Uno. Different operations were performed based on the given instructions. In addition to this, the Arduino Uno was responsible for reading input from the sensors. The Arduino Uno was used as the system platform as the microcontroller board while the SIM900 GPRS/GSM module was used to communicate between the microcontroller unit and the mobile unit. The system could be installed at any place and could be controlled by any mobile phone supporting the SMS service. The mobile phone neither needs to have any special features nor hardware nor any special application to use the system. The system consists of two sensors which are used as heat detector, motion detector to detect motion as the presence of intrusion.